What do Students Need to Know? How About the Idea of Progress ? - Pickus, David (UI Scholars Hub, 2011)
Studying Archeology needs an understanding of the idea of progress. The concept of progress was popular in the 1920s, and it was not for Archeology alone, but it became a new intellectual understanding of the world. “The idea of progress is one of the fundamental notions grappled by civilizations with a historical sense“. “Does this change in the use of metals equal development?,” reminds us to the Xuanyuan era where stone was used to make weapon, whereas jade in the time of Huangdi, and bronze in the time of Yu. This shows that Archeology is related to history and some social institutions, besides applying biochemical analysis to an artifact. As an example of a multi disciplinary archeological research was found in the hypothesis of Why the West rules – for now, by Ian Morris, 2010, which states that the Mediterranean region has the most advanced economic achievement compared to the other regions. The conclusion of which was drawn from analysis of shipwrecks in the Mediterranean ocean and the level of lead in the soil. The concept of progress in this case was the implication of a synthesis contributed from the perspective of several disciplines, or consilience. Thus, the artifacts of the past should be interpreted contextually, and so were the present materials. The values of which will have never been lesser or better in the light of progress.